Leptospira interrogansinfection of southern tamanduas (Tamandua tetradactyla, Linnaeus, 1758) in Brazil - Sousa, Monica S.; Cristiny Rodrigues Silva, Maria Luana; Azevedo, Sergio Santos; Araujo Junior, Joao Pessoa [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; Lima Nascimento, Harlan Hallamys; Kommers, Glaucia Denise; Lopes Nery, Thiago Ferreira; Lucena, Ricardo Barbosa (Wiley-Blackwell, 2020)
Leptospirosis is a zoonotic disease of global importance caused by an obligate aerobic spirochaete that infects a wide variety of domestic and wild animals. Natural hosts are asymptomatic or show moderate signs of the disease. Accidental hosts develop a severe, often lethal, form of the disease. All young southern tamanduas died suddenly at the zoo in the city of Joao Pessoa, Brazil. The animals were found dead without any noticeable clinical signs. Necropsy revealed extensive haemorrhage in the subcutaneous tissues, kidneys, lungs in addition to the presence of red fluid in the thoracic, abdominal and pericardial cavities. Histopathology of kidneys exhibited acute interstitial nephritis and tubular necrosis. Immunohistochemical staining revealed typical leptospiral wavy forms and aggregates in the lumen of several kidney tubules and lungs. Pathological and molecular investigations confirmedLeptospira interrogansinfection. The adult tamanduas did not present with clinical alterations. To our knowledge, this investigation is the first study to report that leptospirosis should be considered as a possible cause of death in tamanduas. This article warns of the risks of anthropization with respect to Leptospira transmission to tamanduas, other animals and humans.
Keywords: collared anteater; infection; Leptospira; pathology; zoonosis